Adhesive and Injectable Hydrogel Microspheres for Inner Ear Treatment (Small 36/2022). Issue 36 (8th September 2022) - Chen, Kaili; Wang, Fei; Ding, Rui; Cai, Zhengwei; Zou, Tianyuan; Zhang, Andi; Guo, Dongye; Ye, Bin; Cui, Wenguo; Xiang, Mingliang
Abstract : Inner Ear Therapy In article number 2106591, Bin Ye, Wenguo Cui, Mingliang Xiang, and co‐workers construct a mussel‐inspired injectable hydrogel microsphere loading Ebselen liposomes that adheres to the cochlea round windows membrane (RWM). The positively charged primary amine groups through electrostatic interaction and the catechol groups through high‐strength coordination bonds and hydrogen bonds adhere to the RWM. This adhesion can prolong the retention of the middle ear cavity for more than 7 days and helps with inner ear therapy.